Low‐grade neuroepithelial tumor: Unusual presentation in an adult without history of seizures. Issue 5 (26th July 2018) - Riva, Giulio; Cima, Luca; Villanova, Manuela; Ghimenton, Claudio; Sina, Sokol; Riccioni, Luca; Munari, Giada; Fassan, Matteo; Giangaspero, Felice; Eccher, Albino
Abstract : Low‐grade neuroepithelial tumors (LGNT) show a broad histopathological spectrum and may be difficult to classify using current World Health Organization (WHO) criteria. A 57‐year‐old man came to medical attention because of headaches. The patient medical history was otherwise unremarkable. Magnetic resonance imaging (MRI) revealed a 2.5 cm lesion, partially cystic, with an increased signal on T2‐weighted imaging, located in the right frontal lobe. The patient underwent right frontal craniotomy and the surgical specimen was entirely evaluated. Microscopic examination showed a tumor arranged predominantly in sheets and nests, with an infiltrative growth pattern and oligodendroglioma‐like appearance. Tumor cells were round to oval with cytoplasmic clearing, hyperchromatic nuclei and inconspicuous nucleoli. Only one mitosis was identified. Necrosis was absent. Differential diagnostic considerations included oligodendroglioma, clear cell ependymoma, polymorphous low‐grade neuroepithelial tumor of the young (PLNTY) and long‐term epilepsy‐associated tumor with clear cell morphology. Neoplastic cells showed positivity for glial fibrillary acidic protein (GFAP), oligodendrocyte transcription factor 2 (OLIG2), α‐thalasemia X‐linked mental retardation syndrome (ATRX) (retained nuclear expression) and CD34. Epithelial membrane antigen (EMA), neuronal nuclear antigen, microtubule‐associated protein‐2e, cyclo‐oxygenase‐2, chromogranin A and isocitrate dehydrogenase 1 (IDH1) (R132H) were negative. Ki‐67 labeling index was 2–3%. Molecular analysis identified neither IDH1/IDH2 mutations nor 1p19q codeletion. Rapidly accelerated fibrosarcoma homolog B1 (BRAF) V600E mutation was also absent by both molecular and immunohistochemical testing. Polymerase chain reaction analysis revealed the presence of fibroblast growth factor receptor 3 (FGFR3)‐transforming acidic coiled‐coil (TACC) fusion. Taken together, the morphological, immunohistochemical and molecular findings supported the final diagnosis of PLNTY.